Inter -and intraobserver variation of ultrasonographic cartilage thickness assessments in small and large joints in healthy children - Stenbøg Elisabeth; Andersen Niels; Pfeiffer-Jensen Mogens; Spannow Anne; Herlin Troels (BMC, 2009)
Abstract Background There is an increasing interest among pediatric rheumatologist for using ultrasonography (US) in the daily clinical examination of children with juvenile idiopathic arthritis (JIA). Loss of joint cartilage may be an early feature of destructive disease in JIA. However, US still needs validation before it can be used as a diagnostic bedside tool in a pediatric setting. This study aims to assess the inter- and intraobserver reliability of US measurements of cartilage thickness in the joints of healthy children. Methods 740 joints of 74 healthy Caucasian children (27 girls/47 boys), aged 11.3 (7.11 - 16) years were examined with bilateral US in 5 preselected joints to assess the interobserver variability. In 17 of these children (6 girls/11 boys), aged 10.1(7.11-11.1) years, 170 joints was examined in an intraobserver sub study, with a 2 week interval between the first and second examination. Results In this study we found a good inter- and intraobserver agreement expressed as a coefficient of variation (CV) less than 10% in the knee (CV = 9.5%interobserver and 5.9%intraobservserI, 9.3%intraobserverII respectively for the two intraobserver measurements) and fairly good for the MCP joints (CV = 11.9%interobserver, 12.9%intraobserverI and 11.9%intraobsevrerII). In the ankle and PIP joints the inter- and intraobserver agreement was within an acceptable limit (CV<20%) but not for the wrist joint (CV>26%). We found no difference in cartilage thickness between the left and right extremity in the investigated joints. Conclusion We found a good inter -and intraobserver agreement when measuring cartilage thickness with US. The inter- and intraobserver variation seemed not to be related to joint size. These findings suggest that positioning of the joint and the transducer is of major importance for reproducible US measurements. We found no difference in joint cartilage thickness between the left and right extremity in any of the examined joint of the healthy children. This is an important finding giving the opportunity of using the non-affected extremity as a reference when assessing articular joint cartilage damage in JIA.